2022
DOI: 10.1007/s10668-022-02594-y
|View full text |Cite
|
Sign up to set email alerts
|

Does industry convergence between agriculture and related sectors alleviate rural poverty: evidence from China

Abstract: Enhancing the synergies between agriculture and related sectors in rural areas is considered an important development strategy to eliminate rural poverty. This article provides evidence for this view by analyzing the effect of industry convergence between agriculture and related sectors on rural poverty. Based on China’s provincial panel data, we use two-way fixed effects model, system generalized method of moments and panel-corrected standard error estimator to quantitatively assess this effect. We find that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, a higher degree of agricultural development, logistics, and ecological environment fosters the evolution of the rural older adult care service industry (58). Specifically, superior agricultural development levels supply ample production factors to the rural older adult care service industry, spurring integration between industries (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher degree of agricultural development, logistics, and ecological environment fosters the evolution of the rural older adult care service industry (58). Specifically, superior agricultural development levels supply ample production factors to the rural older adult care service industry, spurring integration between industries (59).…”
Section: Discussionmentioning
confidence: 99%
“…Measured by the ratio of agricultural added value to regional GDP in each province, this soft indicator has a profound impact on the rural older adult care service industry. At the same time, promoting the integration of the modern service industry and agriculture is an effective way to improve the development of the rural older adult care service industry (59).…”
Section: Control Variables (1) Living Standards Of Rural Residents (L...mentioning
confidence: 99%
“…This is an adjusted approach to carrying out regressions with panel data when the disturbances are heteroskedastic and contemporaneously correlated across panels [61]. This methodology is supported by the scientific literature [62][63][64][65][66], based on the study of Beck and Katz [67], because with heteroscedasticity, cross-sectional dependence, and autocorrelation, the OLS (ordinary least squares) regressions are not efficient.…”
Section: Methodsmentioning
confidence: 99%
“…In the studies on rural tourism and poverty vulnerability, a sustainable livelihood model covering human, natural, material, social, and other capital factors has been preliminarily constructed to evaluate the risk of rural households falling back into poverty [44,45]. Studies have shown that most rural households are vulnerable [46], and rural tourism can change the traditional livelihood mode of rural areas [47] and integrate tourism resources [48] and other ways to improve the overall livelihood capital of rural households [49], and achieve multi-dimensional poverty reduction such as economy, education [50], living standards [51], and housing and employment [52], thereby reducing the risk of rural households falling back into poverty.…”
Section: Literature Reviewmentioning
confidence: 99%